The Baltic Peoples in the Development of Virgin Lands in Kazakhstan: Cultural Relations and Standards / Deviations in Everyday Life (The 1950s–1960s) - Mazhitova, Zhanna; Amrina, Minar; Saktaganova, Zauresh; Kozina, Valeria; Yeleukhanova , Svetlana; Balykova, Akkaiyn (Journal of Ecohumanism, 2024)
This article aims to investigate the issues of “standards and deviations” in the everyday life of the Baltic peoples who came to Kazakhstan for the development of virgin and fallow lands in the 1950s and 1960s. The authors attempted to trace the history of the appearance of the Baltic peoples on the territory of Kazakhstan, as well as issues of “standards and deviations” in everyday life during the years of virgin lands development. The study focuses on the fact that assistance from the Baltic republics to virgin land Kazakhstan with human and material resources has become the norm of the Soviet everyday life. The state and party organs imperatively implemented the standards of contribution and “behaviour” of the Soviet republics in the implementation of the virgin project, shaping various positive/negative socio-cultural everyday practices. According to the authors, the Soviet leadership created “deviations” in the form of protest sentiments, inter-ethnic conflicts and discontent of national minorities on a wide range of political and socio-economic issues through ideological principles.